Money, expectations and the existence of a temporary equilibrium - HOOL, Bryce (Institutional Knowledge at Singapore Management University, 1976)
The article presents information on money, expectations and the existance of a temporary equilibrium. If money and financial assets are to be integrated into general equilibrium theory, it is apparent that the classical Arrow-Debreu framework must be modified. As long as all trading takes place essentially at some initial point in time, with each individual subject only to a present value budget constraint, there is no place in the system for money, either as a medium of exchange or as a store of value, even if uncertainty about future states of the world is introduced as in G. Debreu's work, for example. It is natural then to consider an economy with sequential trading, and the appropriate Walrasian equilibrium concept becomes the Hicksian temporary equilibrium. In this article it is shown that, if the actual "Clower" constraint is used to introduce into the Wairasian model the requirement that money be used as the medium of exchange, it is possible to demonstrate the existence of a temporary monetary equilibrium (TME), with a much weaker restriction on expectations. More precisely, it is shown that the class of price expectations consistent with the existence of a TME includes expectations with elasticity up to and including unity. If the expenditure constraint is added to the basic Patinkin model we can establish the existence of a short-run equilibrium in that model, subject to a mild condition on initial endowments expressing the desirability of an intertemporal transfer of wealth.